Networking and Security Measures - Gupta, Vaibhav; Goswami, Sumit; Kumar, Ashok; Singh, Mohinder (DESIDOC Journal of Library & Information Technology, 2003)
By writing this paper a small effort has been put to understand the growing network needs and its security. Various types of network threats and security services are discussed. This will help in designing a secure and robust network infrastructure by discussing management security policies and risk analysis. http://dx.doi.org/10.14429/dbit.24.2.3621